Internationalizing higher education: from grand plans to evolving responses - Mertkan, Sefika; Gilanlioglu, Ilkay; McGrath, Simon (Emerald, 2016)
Purpose – This paper explores the complexity of developing into an international institution from the perspective of higher education leaders through the case study of one institution engaged in institutional transformation.